Two-phase linear relationship of Vitamin D and Vitamin A among children aged 0–14 years: a cross-sectional study - Liu, Wenyuan; Wang, Qiao; Mao, Bibo; Xu, Fei; Ke, Yefang; Zhang, Shengying; Zhou, Chenbo; Liu, Chunyan; Lu, Wenbo; Zheng, Jishan (Frontiers in Nutrition, 2025)
BackgroundVitamin D and Vitamin A are crucial for children’s immune function, bone health, and cellular growth, but their interrelationship and the impact of various factors remain poorly understood.ObjectiveTo explore the relationship between Vitamin D and Vitamin A levels in children and identify any critical thresholds.MethodsA cross-sectional study was conducted from 2018 to 2021 in Ningbo, Zhejiang, China. Participants were children aged 0 to 14 years attending community health service centers for routine health check-ups. Multivariate linear regression analysis was conducted to ascertain the association between serum Vitamin D and Vitamin A levels. A smooth curve fitting approach was employed to analyze the dose–response relationship between Vitamin D and Vitamin A.ResultsA total of 4,752 participants were included. The study revealed significant variations in baseline Vitamin D and Vitamin A levels across different deficiency categories. Mean Vitamin D levels were lowest in the severe deficiency group (4.9 ng/mL) and highest in the normal group (34.8 ± 9.8 ng/mL), while mean Vitamin A levels were lowest in the deficiency group (226.6 ± 72.2 ng/mL) and highest in the normal group (263.3 ± 74.0 ng/mL). The study revealed a two-phase linear relationship with a significant threshold effect at a Vitamin D level of 28.289 ng/mL. Below this threshold, the association between Vitamin D and Vitamin A was strong (β = 2.935, 95% CI: 2.173, 3.696), while above the threshold, the association was significantly weaker (β = 0.737, 95% CI: 0.413, 1.061). The likelihood ratio test confirmed the significance of this threshold effect (p < 0.001).ConclusionThe study concludes that a significant threshold at 28.289 ng/mL Vitamin D marks a point beyond which the association with Vitamin A levels plateaus, highlighting the importance of this threshold for optimizing vitamin status in children.